Interferon-Stimulated Genes and Immune Metabolites as Broad-Spectrum Biomarkers for Viral Infections - Chien-Hsin Huang; Maudry Laurent-Rolle; Tyler L. Grove; Jack Chun-Chieh Hsu (Viruses)
The type I interferon (IFN-I) response is a critical component of the immune defense against various viral pathogens, triggering the expression of hundreds of interferon-stimulated genes (ISGs). These ISGs encode proteins with diverse antiviral functions, targeting various stages of viral replication and restricting infection spread. Beyond their antiviral functions, ISGs and associated immune metabolites have emerged as promising broad-spectrum biomarkers that can differentiate viral infections from other conditions. This review provides an overview of the diagnostic potential of ISGs at transcript and protein levels, as well as their immune metabolites. We focus on their clinical applications and the sensitivity and specificity of these biomarkers through receiver operating characteristic (ROC) analysis. We highlight the need for further research to facilitate the effective translation of these biomarkers into clinical practice.